FACTORS ASSOCIATED WITH COMPLICANCE IN PREGNANT WOMEN TAKING FE TABLET IN PUSKESMAS KUTA BAHARU,KOTA BAHARU DISTRICT,ACEH SINGKIL DISTRICT 2023 - Rahmani Suriono; Yasrida Nadeak; Repi Mariska Purba (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Pregnant women are the result of fertilization from sperm which causes the mother to carry a fetus in her womb, namely in her uterus. In this study the number of samples based on the formula with the total population and samples totaled 37 samples. Sampling using slovin formula. The results showed that there was a relationship between knowledge and adherence to consuming Fe tablets in pregnant women with a p-value of 0.001 <0.05, the role of health workers with a p-value of 0.009 <0.05, family support with a p-value of 0.006 <0. 05 and ANC with a p-value of 0.002 <0.05 associated with adherence to consuming Fe tablets in pregnant women. There is a relationship between knowledge and adherence to consuming Fe tablets in pregnant women with a p-value of 0.001 <0.05. There is a relationship between the role of health workers and adherence to consuming Fe tablets in pregnant women with a p-value of 0.009 <0.05